256. Synthesized 2D image reconstruction from Digital Breast Tomosynthesis (DBT). (December 2018) - Piergentili, M.; Zefiro, D.; Ielo, F.; Foppiano, F.; Boccacci, P.
Abstract : Purpose: Although DBT provides 3D insight into the breast, the community agrees on the necessity of two-dimensional images to facilitate comparison with previous examinations and the evaluation of microcalcifications. For this reason, more projections (at zero degree) are acquired, to provide the radiologist a conventional two-dimensional digital mammographic (DM) image. This method is often called "combo-mode" acquisition and the additional projections lead to almost double the Mean Glandular Dose (MGD). The 3D tomographic reconstruction technology of the volume under examination is based on the acquisition of images at different angles, – in this case 13 projections are used between −20 and 20 degrees – with a short-time scan. In this reconstruction process, the images are affected by artefacts that may affect the lesion identification process. Tomosynthesis, therefore, is able to identify the position of a lesion but is disturbed by artifacts. The purpose of this work is to reconstruct the zero degree projection of DBT in order to obtain a synthesized two-dimensional image with an in-house software. Methods: The raw image from the central projection is processed through a denoising software based on a pyramidal decomposition of the image, a filtering by thresholding, and subsequent reconstruction of the image itself. The optimization of reconstruction parameters has been tested on the acquisition of a 45 mm thick PMMA phantom which contains 0.1 mm sheet of aluminium 1 cm 2 . Results: A threshold parameter was identified for the denoising process for the reconstruction of the phantom and applied to clinical images. A good depiction of the microcalcifications has been found. Conclusions: The proposed method offers the possibility of processing the tomosynthesis projection images and get similar results compared to DM image, without further radiation dose to the patient. The processing is very fast and can be performed during the DBT reconstruction time.